Free Jazz Communism, Sezgin Boynik and Taneli Viitahuhta - Grundy, David; Crépon, Pierre (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2021)
This review addresses the book 'Free Jazz Communism' (Rab Rab Press), a volume concerning a performance at the 1962 World Youth Festival in Helsinki by the Archie Shepp-Bill Dixon group. The book argues that this hitherto neglected event is a central moment for studies of the relation between jazz and politics during the Cold War Era, combining source texts, interviews, and polemical interventions to make its case. Our review fills in some of the details about the event, and Shepp's political activity during the early 1960s, which are not uncovered in the book. The first half of the review concentrates on our research into the festival, and the second half turns more closely to the book itself, as well as to Shepp's involvement with political causes during this time. Our intention is to use the book as an occasion to stage original research, as well as to analyse the contributions and shortcomings of the book itself.